Microeconomics - "Gwartney, James D." (New York, 1977)
Economics is on the front page of our current day newspapers. Economic issues usually occupy the center stage of our political campaigns, Knowledge of economics is essential to the understanding of social problems such as poverty, discrimination, pollution, unemployment, and the power of special interest groups. Despite its importance, objectivity forces one to admit that economic literacy in the United States is low. The analysis of our political entrepreneurs, editorial writers, and news commentators often contains elementary economic fallacies. These fallacies usually go unnoticed and unchallenged
Keywords: Microeconomics